Yan Ping’s artwork from semantic perspectives - Peng Yaxin; Junior Kimwah; Mohammad Puad Bebit (Penerbit Universiti Malaysia Sabah, 2025)
Yan Ping is a Chinese painter. The most used paint medium is oil paint, and he was a pioneer in oil painting in the country. His dynamic and colour-filled paintwork stood out to be his identity. This study was done to identify the meaning that Yan Ping wanted to convey. The method of analyzing works is carried out through a semantic approach that emphasizes the implicit meaning by using visual images. Yan Ping is smart in applying meaningful images in his work. With his artistic style, this makes his oil paintings are well-respected and sell at a high price.